Distribution of the impact of monetary and fiscal policy instruments by technological modes and sectors of the economy - O. S. Sukharev; O. N. Afanasyeva (Финансы: теория и практика, 2023)
The subject of the study is the impact of monetary and fiscal policy instruments on the functioning of the structural elements of the economy, represented by sectors and technological structures. The purpose of the paper is to establish how the monetary and individual fiscal policy instruments influenced the structure of the Russian economy. The methodology consists of the “distributed control” doctrine, which modifies Tinbergen’s principle of “goals-instruments” of macroeconomic policy, since it allows to reveal the unequal power of the instrument by objects of economy, structural and empirical analysis, correlation-regression analysis, with which it is possible to show a picture of the distributed influence of monetary and fiscal policy instruments. A general algorithm of research and application of the doctrine of “distributed management” at the macroeconomic level are developed — by technological structures and economic sectors, which made it possible to obtain a picture of the distribution of the influence of monetary policy on economic objects, to identify the significance of individual fiscal policy instruments. The general result of the research is that the doctrine of “distributed management” used not only modifies the classical theory of economic policy, but also confirms that, in addition to the economic structure, the impact structure of standard monetary and fiscal policy instruments arises. The distribution of the most significant instruments of monetary and fiscal policy by technology and three sectors of the Russian economy to ensure its growth in the period 2011–2021 are obtained. It was found that the development of high-level processing and technological modes were more influenced by monetary than budgetary instruments, and the transfer of resources to the national welfare fund hindered their development. Fiscal policy measures — revenues, expenditures, budget deficit/surplus — did not have an equal impact on the development of the considered sectors of the economy. The prospect of further research is to develop a software module that includes ongoing analysis and automates calculations based on available statistics to change of monetary and fiscal policy measures in Russia aimed at developing the manufacturing sector and high-tech.